أثر الإبتكار المالي على إجمالي الودائع المصرفية دراسة قياسية للبنوك العاملة في الأردن للفترة(2012-2021) - بوجمعة, ياسين; دادن, عبد الغفور (جامعة الوادي - University of Eloued, 2023)
The study aimed to measure the impact of financial innovations on the total bank deposits in banks operating in Jordan for the period (2012-2021), based on the annual reports of the Central Bank of Jordan, and the study concluded that the number of ATMs and the number of points of sale (POS) are the most influential factors on the total deposits of banks operating in Jordan during the study period at a level of 5%. compared to the other indicators of financial innovation represented by the number of Electronic Clearing Cheques (ECC) and the number of payment orders through the Instant Total Settlement System (RTGS) which were non-significant, According to the estimated model and the (VECM) method used, there was also certainly a long-term balanced relationship among (ATMS), (POS) and the Total Bank Deposits at the level of the banks operating in Jordan
The impact of financial innovation on total bank deposits A standard study for banks operating in Jordan for the period (2012-2021
مقال
Keywords: الإبتكار المالي، إجمالي الودائع، البنوك التجارية; financial innovation, Total Deposits, commercial banks